Design, Synthesis and Crystal Structure Analysis of Co(II) and Cd(II) Coordination Compounds with Benzimidazole Derivative Ligands - Sun, Dan; Pan, Ke-Qi; Xu, Hai-Jun (Asian Journal of Chemistry, 2014)
Two benzimidazole complexes of Cd(II) and Co(II) (1 and 2) were synthesized and characterized by single-crystal X-ray diffraction. The structure analysis indicates that the Cd(II) complex belongs to tetragonal P41212 space group with a = 0.85006 (17) nm, b = 0.85006 (17) nm, c = 2.9594 (6) nm, V = 2.1385 (7) nm3, Z = 4. Each Cd(II) atom coordinates with two benzimidazole derivative ligands and two nitrate anions in the shape of coordination polyhedron existing between the dodecahedron and tetragonal antiprism. In the crystal structure, the adjacent coordination units were connected together through strong intermolecular N-H···O H-bonding interactions, which result in the formation of a two-dimension supramolecular structure. For the Co(II) complex with chiral ligand, the same handedness structure was formed and crystallized in the orthorhombic P212121 space group with a = 0.80052 (6) nm, b = 1.39487 (8) nm, c = 1.529340 (10) nm, V = 1.70769 (16) nm3, Z = 4. Each Co(II) atom coordinates with one benzimidazole derivative ligand and two chlorides in distorted tetrahedron geometry.